Geomorphic Effects of Flooding Along Reaches of Selected Rivers in the Saguenay Region, Québec, July 1996 - Brooks, G.; Lawrence, D. (Géographie physique et Quaternaire, 2000)
Abstract A severe rainstorm from July 18 to 21, 1996, caused widespread flooding along many rivers in southern Québec, particularly in the Lac-Saint-Jean-Chicoutimi area, along north-flowing tributaries of the Rivière Saguenay. Along study reaches located on the Rivière aux Sables, Rivière Chicoutimi, Rivière du Moulin and Rivière à Mars, the fluvial geomorphic effects of flooding varied considerably, reflecting differing channel morphologies (alluvial, non-alluvial and bedrock), flow energy, and the interaction of floodwaters and infrastructure. Catastrophic channel widening and floodplain reworking occurred along the Rivière à Mars study reach, transforming the river from a meandering to braided planform. Consistent with this, unit stream power of the flood flow exceeded the minimum erosive threshold (300 Wm- 2 ) along most of the study reach. Morphological and empirical evidence indicates that the pre-flood Rivière à Mars channel exhibited a transitional planform, and thus was vulnerable to a planform transformation during an extreme flood. The most significant geomorphic effects along the Rivière aux Sables and Rivière Chicoutimi study reaches occurred at a number of run-of-the-river dams. Floodwaters overtopped four dams and eroded deeply into unconsolidated sediments adjacent to the dams, forming new channels that captured the flow of the river. Floodwaters also overtopped a fifth dam, scouring overburden and road beds, and damaging and destroying buildings within an urban subdivision. Elsewhere along these two rivers, as well as along the Rivière du Moulin study reach, there were localized erosional problems, particularly at bridges, but the geomorphic effects generally were limited or negligible, reflecting either low unit stream power or resistant substrates.